Recombinant human soluble thrombomodulin and mortality in severe pneumonia patients with sepsis‐associated disseminated intravascular coagulation: an observational nationwide study. (11th December 2014) - Tagami, T.; Matsui, H.; Horiguchi, H.; Fushimi, K.; Yasunaga, H.
Summary Background The association between recombinant human soluble thrombomodulin (rhTM) use and mortality in patients with sepsis‐associated disseminated intravascular coagulation (DIC) remains controversial. Objectives To examine the hypothesis that rhTM could be effective in the treatment of patients with sepsis‐associated DIC following severe pneumonia. Methods Propensity score and instrumental variable analyses using a nationwide administrative database, the Japanese Diagnosis Procedure Combination inpatient database, were used. The main outcome was 28‐day in‐hospital all‐cause mortality. Results Eligible patients (n = 6342) from 936 hospitals were categorized into the rhTM group (n = 1280) or control group (n = 5062). Propensity score matching created a matched cohort of 1140 pairs with and without rhTM. No significant difference in 28‐day mortality was documented between the two groups in the unmatched analysis (rhTM vs. control, 37.0%, 474/1280 vs. 36.9%, 1866/5062; odds ratio [OR], 1.00; 95%CI, 0.98–1.03), nor in the propensity‐matched analysis (37.6%, 429/1140 vs. 37.0%, 886/1140; OR, 1.01; 95%CI, 0.93–1.10). The logistic regression analysis did not show a significant association between the use of rhTM and 28‐day mortality in propensity‐matched patients (OR, 1.00; 95%CI, 0.87–1.22). An analysis using the hospital rhTM‐prescribing rate as an instrumental variable found that receipt of rhTM was not associated with reduction in mortality at 28 days (risk difference, 0.008; 95% CI, −0.08–0.98). Conclusions This large retrospective nationwide study demonstrated that there might be little association between the use of rhTM and mortality in severe pneumonia patients with sepsis‐associated DIC. A multinational randomized trial is required to confirm this.